Autoethnographic Dance and Transformative Learning: Exploring Self-Reflexive Identity Work and Change. (April 2021) - Baldwin, Cheryl K.; Motter, Alyssa E.
This retrospective case study investigated how learners in a transformative autoethnographic dance course engaged in and navigated self-reflexive identity work and corresponding learning outcomes. Data were drawn from 15 diverse undergraduate students enrolled in a course for credit at an urban community college. Findings indicated that learners used choreographic motifs to evoke emotional aspects of a biographic experience and to manage their emotional vulnerability. Learners differed in their self-disclosure, types of reflection, and degree of resolution in their dance narratives. Transformation of identity was found for one third of the class with evidence of change both from exploration of preconscious emotions and epistemic change in perspective.